Neotipification of Behria tenuiflora Greene (Alliaceae) - León de la Luz, José Luis; Pérez Navarro, José Juan (Instituto de Ecología, A.C., 2004)
Behria tenuiflora Greene is an endemic taxon of the southern part of the Baja California peninsula, Mexico. The wild populations are distributed in an altitudinal range from the top of the mountains at 2200 m to practically the sea level. In this paper we neotypify B. tenuiflora since the type specimen is lost. A detailed description and an illustration of the plant are included.